Discordance between karyotype from amniotic fluid and postnatal lymphocyte cultures - Bizzoco, Domenico (Journal of prenatal medicine, 2012)
Discordance between karyotype seen from amniocentesis and from neonatal blood is a very unusual condition with different possible causes.We present a case of discordance between prenatal cytogenetic diagnosis from amniotic fluid and post-natal cytogenetic diagnosis from lymphocyte cultures